Kiwa-kiwa handbook for community animators. (Quezon City Basic Christian Communities-Community Organizing, Philippines, 1991)
This handbook is intended to guide community workers in bringing educative workshops to barrios. It gives step by step encouraging adaptations and creates initiatives. It also uses thought-provoking drawings that uses humor and wit.
Gives a concise form of plans and explanations about doing a serious formation plan. Provides verses and phrases from the Bible about community building. A module with a variety of topics discussed from the practical to the more theoretical, from being religious to being secular in building a productive and spiritual community.
Keywords: Religious education -- Philippines -- Handbooks, manuals, etc; Christian communities -- Philippines